AS POLÍTICAS PÚBLICAS NA PERSPECTIVA DA DESIGUALDADE NO NOROESTE COLONIAL GAÚCHO - Allebrandt, Sérgio L.; Siedenberg, Dieter R.; Ceratti, Larissa L.; Filho, Carlos J. M.; Dallepiane, Sabrina; Porciúncula, Juliana; Wesendonk, Claudia (Salão do Conhecimento, 2013)
Resumo